Bimodal linear low-density polyethylene as well as preparation and application thereof

The bimodal linear low-density polyethylene prepared through Ziegler-Natta catalyst and multi-stage reaction process solves the shortcomings of the existing LLDPE in terms of processing performance and sealing properties, achieves excellent mechanical properties and processing properties, is suitable for heavy packaging film and other fields, and reduces the use of polyethylene raw materials.

CN119912614APending Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311431182.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing linear low-density polyethylene (LLDPE) has shortcomings in processing performance and sealing properties, especially in the case of processability and mechanical properties of B-LLDPE copolymers prepared using bimodal catalyst systems, it is difficult to achieve the performance combination of single-peak Zn-LLDPE and MCN-LLDPE in terms of processability and mechanical properties.

Method used

Using Ziegler-Natta-type catalyst, a bimodal linear low-density polyethylene with a density in the range of 0.915-0.930 g/cm3 was prepared by a combination of prepolymerization reaction, ring tube reaction and gas phase reaction, and its melting index and flow rate ratio were controlled to improve its processing performance and mechanical properties.

Benefits of technology

The performance optimization of bimodal linear low-density polyethylene has been achieved, with good processing and mechanical properties, including improved tear resistance, tensile strength and dart impact strength, and can thin the use of polyethylene raw materials in the production of heavy packaging films, achieving energy saving and consumption reduction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses bimodal linear low-density polyethylene with the density of 0.915-0.930 g / cm < 3 > and a preparation method and application thereof, and the method comprises the following steps: 1) ethylene, butylene, hydrogen, a catalyst and triethyl aluminum in a certain weight ratio are subjected to a prepolymerization reaction under the conditions of 6.4 MPa and 70 DEG C to obtain a prepolymer; (2) carrying out loop reaction on the prepolymer in the step (1) under the conditions of 6.4 MPa and 85 DEG C, and adding hydrogen, ethylene, butylene and triethyl aluminum to obtain a loop reaction polymer; and (3) carrying out gas-phase reaction on the loop reaction polymer in the step (2) under the conditions of 2.0 MPa and 80 DEG C, and adding hydrogen, ethylene and butylene in a molar ratio of (4-10): 1000: (600-700) to obtain the bimodal linear low-density polyethylene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to polyethylene copolymers, and more particularly to bimodal linear low-density polyethylene copolymers and preparation and application thereof. Background Art

[0002] Linear low density polyethylene ("LLDPE") differs in composition from low density polyethylene ("LDPE") and has certain superior properties that have allowed it to replace LDPE in many commercial applications. These applications include films, sheets, and injection molded articles. LLDPE films and sheets are used in packaging applications and non-packaging applications. Examples are agricultural film, food packaging, garment bags, grocery bags, heavy duty sacks, industrial sheets, pallets and shrink wrap, and bags. LLDPE injection molded articles include buckets, freezer containers, closures, and toys.

[0003] US7576166B2 relates to a method for preparing a linear low density polyethylene composition using a Ziegler-Natta catalyst, and includes a method for preparing a bimodal linear low density polyethylene polymer composition for preparing a film.

[0004] US8846188B2 and US8957158B2 relate to impact resistant LLDPE compositions and films made therefrom. Polyethylene is produced in a gas phase reactor.

[0005] WO20069637A2 relates to low density polyolefin resins having low molecular weight and high molecular weight components, and films prepared therefrom. Vinyl polymers prepared using a dual metallocene catalyst system.

[0006] Each grade of LLDPE has been improved to provide ease of processing and improved mechanical strength and toughness, such as melt strength, low tan delta values ​​and a wide range of z-average molecular weight / weight-average molecular weight (Mz / Mw) values, as measured by extruder barrel pressure and rheological testing, such as shear thinning, among other properties.

[0007] Bimodal linear low density polyethylene copolymers (B-LLDPE copolymers) that solve many of the problems associated with -olefin copolymers. The manufacture, uses and properties of prior art LLDPE prepared with metallocene catalysts ("prior art MCN-LLDPE"). B-LLDPE copolymers further address needs in the manufacture, uses and properties of resin blends that include LLDPE prepared with Ziegler-Natta catalysts and prior art MCN-LLDPE. For example, prior art MCN-LLDPE has poor processability relative to the processability of prior art LLDPE prepared with Ziegler-Natta catalysts ("prior art Zn-LLDPE"). For example, during the extrusion process of prior art MCN-LLDPE, the extruder barrel pressure is higher than the pressure during the extrusion process of prior art Zn-LLDPE.

[0008] Moreover, relative to existing Zn-LLDPE, existing MCN-LLDPE may have insufficient sealability (e.g., heat seal / hot tack may be too weak). Other processability defects of existing MCN-LLDPE may include tan values ​​that are too high, a narrow Z-average molecular weight over a weight average molecular weight (Mz / Mw) value range, a molecular weight distribution (MWD), such as a molecular weight distribution that is less than the weight average molecular weight, and a shear thinning index value that is too low.

[0009] The B-LLDPE copolymers in the prior art WO2021202483A1 and WO2021202486A1 provide technical solutions to the above problems, wherein the B-LLDPE copolymer has at least one processing performance characteristic similar to that of unblended unimodal Zn-LLDPE and at least one stiffness / mechanical property similar to that of unblended unimodal MCN-LLDPE. The B-LLDPE copolymer is prepared using a bimodal catalyst system, and products prepared therefrom, methods for preparing and using the copolymer, and articles comprising the copolymer are provided. The B-LLDPE copolymer has an improved combination of properties, including at least one processing performance characteristic similar to that of unblended unimodal Zn-LLDPE and dart impact performance similar to that of unblended unimodal MCN-LLDPE.

[0010] The present invention utilizes Ziegler-Natta catalyst to produce and develop bimodal linear low-density polyethylene film material, which is mainly used for heavy packaging film production and processing. It not only improves the situation that the linear bimodal low-density polyethylene film material used for heavy packaging film production in the domestic market mainly relies on imports, but also the bimodal linear low-density polyethylene film material developed by the present invention has superior performance and lower cost. Summary of the invention

[0011] The present invention uses a certain amount of ethylene, butene and hydrogen monomers to undergo a preliminary reaction in a prepolymerization reactor and then enter a loop reactor. Ethylene, butene and hydrogen are added to the loop reactor and controlled in proportion to produce a 0.951 kg / m 3 The active polyethylene of about 100% is then fed into the gas phase reactor for reaction. The yield ratio of the gas phase reactor is controlled at about 59%, and the final product melt index is controlled at 18-25g / 10min (21.6KG), and the density is 0.918-0.924G / CM 3 Left and right bimodal linear low density polyethylene.

[0012] The technical solution of the present invention is achieved in this way:

[0013] The present invention provides a bimodal linear low-density polyethylene, wherein the density of the bimodal linear low-density polyethylene is 0.915-0.930 g / cm 3 .

[0014] In a preferred embodiment, the bimodal linear low density polyethylene has a density of 0.918-0.924 g / cm 3 .

[0015] In a preferred embodiment, the bimodal linear low density polyethylene has a melt index MFR 21.6 between 18 and 25 G / MIN, a melt index MFR 5 between 0.80 and 1.2 G / MIN, and a flow rate ratio FFR of 20-30.

[0016] The present invention also provides a method for preparing the above-mentioned bimodal linear low-density polyethylene, the method comprising the following steps:

[0017] 1) prepolymerizing ethylene, butene, hydrogen, catalyst and triethylaluminum in a weight ratio of 300-600:30-50:0.1-0.2:300-400:0.3-1.0 at 6.4 MPa and 70° C. to obtain a prepolymer;

[0018] 2) subjecting the prepolymer of step 1) to a ring tube reaction at 6.4 MPa and 85° C., and adding hydrogen, ethylene, butene and triethylaluminum in a molar ratio of 250-350:1000:600-700:0.5-1.0 to obtain a ring tube reaction polymer;

[0019] 3) The polymer obtained in the loop reaction in step 2) is subjected to gas phase reaction at 2.0 MPa and 80° C., and hydrogen, ethylene and butene are added in a molar ratio of 4-10:1000:600-700 to obtain a bimodal linear low density polyethylene.

[0020] The catalyst in step 1) is a Ziegler-Natta type catalyst.

[0021] In a further preferred embodiment, the catalyst in step 1) is transported by nitrogen, and propane is soaked in the catalyst so that the catalyst micropores are filled with propane, and the catalyst enters the prepolymerization reaction under the action of the propane flushing flow.

[0022] In a preferred embodiment, the melt index MFR of the loop reaction polymer in step 2) is

[0023] 21.6: between 250-350G / MIN, density: 0.948-0.953g / cm 3 .

[0024] In a preferred embodiment, the gas phase reaction yield ratio in step 3) is 57-61.

[0025] In another preferred embodiment, the gas phase reaction powder index in step 3) is 16-26 g / 10 min.

[0026] The present invention also provides the application of the bimodal linear low-density polyethylene in the fields of heavy packaging films, electrical and / or optical cable sheathing materials, etc.

[0027] The present invention also provides a heavy packaging film, which comprises the above-mentioned bimodal linear low density polyethylene, linear medium density polyethylene, metallocene linear low density polyethylene and HDPE in a weight ratio of 22:15:50:13.

[0028] In a preferred embodiment, the thickness of the heavy packaging film is ≤0.14 mm.

[0029] In a preferred embodiment, the thickness of the heavy packaging film is 0.12 mm-0.14 mm.

[0030] In a preferred embodiment, the longitudinal tensile strength of the heavy packaging film is 35-36 MPa, and the transverse tensile strength is 28-29 MPa.

[0031] In a preferred embodiment, the heavy packaging film has a nominal strain at break in the longitudinal direction of 755-816%, and a nominal strain at break in the transverse direction of 985-1095%.

[0032] In a preferred embodiment, the heavy packaging film has a longitudinal right-angle tear strength of 167-175 KN / m, and a transverse right-angle tear strength of 256-281 KN / m.

[0033] Technical effects of the present invention:

[0034] Through the organic combination of domestic catalysts and Nordic bimodal processes, the linear bimodal low-density polyethylene produced by the present invention has good mechanical properties such as good dart impact strength, tensile strength and good tear resistance, and good processing performance by controlling the yield ratio of the loop reactor and the gas phase reactor and adding different concentrations of comonomer (butene-1) to the two reactors. This polyethylene product can effectively achieve thinning during the processing and production of heavy packaging bags, and the thickness of heavy bags can be thinned from 0.18MM to 0.12-0.14MM, which can effectively reduce the use of polyethylene raw materials and achieve energy saving and consumption reduction. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as commonly understood by those of ordinary skill in the art to which the invention belongs. Although any methods and materials similar or equivalent to those described herein can be used to implement or test the present invention, preferred methods and materials are described herein. For purposes of the present invention, the following terms are defined below.

[0037] Linear bimodal low density polyethylene

[0038] The linear bimodal low density polyethylene described in the present invention can also be called bimodal linear low density polyethylene.

[0039] Prepolymerization

[0040] The prepolymerization reaction of the present invention is as follows: a Ziegler-Natta type catalyst is transported to a catalyst preparation tank by nitrogen, propane is soaked to fill the catalyst micropores with propane, and the catalyst is metered into a prepolymerization reactor under the action of propane flushing flow, ethylene is added in an amount of 300-600 kg / h, triethylaluminum is added in an amount of 0.3-1.0 kg / h, hydrogen / propane feed ratio is 0.1-0.2 kg / t, butene-1 / propane feed ratio is 30-50 kg / t (the mass ratio or molar ratio between the catalyst and ethylene needs to be given here), and the prepolymerization reaction is carried out under the conditions of a reactor pressure of 6.2-6.6 MPa and a reaction temperature of 65-75° C. A layer of polymer is coated on the surface of the catalyst to prevent a large number of polymer particles from being broken due to a violent reaction after entering the loop reactor to produce a large number of polymer fine powders.

[0041] Ring tube reaction

[0042] The loop reactor of the present invention is that the materials of the prepolymerization reactor enter the loop reactor through the connecting pipeline: the reaction pressure is 6.2-6.6MPA, the reaction temperature is 80-88℃, and the molecular weight is adjusted by hydrogen, the polymer density of the loop is adjusted by butene, the hydrogen / ethylene molar ratio is 250-350MOL / KMOL, the butene / ethylene molar ratio is 600-700MOL / KMOL, and the amount of triethylaluminum added is 0.5-1.0KG / H. Low molecular weight products are produced in the loop reactor, the powder MFR (2.16KG): 250-350G / MIN, density: 0.948-0.953g / cm 3 .

[0043] Gas phase reaction

[0044] The gas phase reaction of the present invention is that the polymer in the loop is partially recycled through flash gas phase, and the active polymer is transported to the gas phase reactor to continue the reaction. The reaction conditions of the gas phase reactor are reaction pressure: 1.8-2.0MPA, reaction temperature: 75-83°C, hydrogen is used to adjust the molecular weight of the final product in the loop reactor, butene adjusts the final density of the product, and the distribution rate controls the molecular weight distribution of the final product. The hydrogen / ethylene molar ratio is 4-10MOL / KMOL, and the C4 / C2 butene / ethylene molar ratio is 600-700MOL / KMOL. The high molecular weight part is produced in the gas phase reactor. The gas phase reactor yield ratio is 57-61, the gas phase reactor powder index is 18-25g / 10min, and the density is 0.920-0.925g / cm3. After the final product produced by the gas phase reactor is inactivated, it enters the extrusion system through the air conveying system for extrusion granulation to form the final polymer particles.

[0045] Table 1

[0046]

[0047] As used herein, the term "about" refers to an amount, level, value, dimension, size, or amount that differs by up to 30%, 20%, or 10% compared to the amount, level, value, dimension, size, or amount of a reference product. Percentages used herein, unless otherwise indicated, are by weight.

[0048] Throughout the specification and claims, unless otherwise required, the following words "comprise" and variations "comprising" and "including" will be understood to imply the inclusion of a stated integer or step, or a group of integers or steps, but not the exclusion of any other integer or step, or other group of integers or steps.

[0049] Example 1: Linear bimodal low density polyethylene

[0050] Ziegler-Natta type catalyst is transported to the catalyst preparation tank by nitrogen, and propane is soaked to fill the catalyst micropores with propane. Under the action of propane flushing flow, the catalyst is metered into the prepolymerization reactor, ethylene addition amount is 300KG / H, triethylaluminum addition amount is 0.3KG / H, hydrogen / propane feed ratio: 0.1KG / T, butene / propane feed ratio: 30KG / T, ethylene / catalyst feed ratio is controlled at 300KG / KG, prepolymerization reaction is carried out at 6.4MPa, 70℃, and a layer of polymer is coated on the catalyst surface to prevent the violent reaction after entering the loop reactor from causing a large number of polymer particles to break and produce a large amount of polymer fine powder.

[0051] The materials in the prepolymerization reactor are connected through a pipeline to enter a loop reactor at 6.4MPa and 85℃ for reaction. Hydrogen is used to adjust the molecular weight, butene is used to adjust the polymer density of the loop, the hydrogen / ethylene molar ratio is 250MOL / KMOL, the butene / ethylene molar ratio is 600MOL / KMOL, and the amount of triethylaluminum added is 0.5KG / H. Low molecular weight products are produced in the loop reactor, polyethylene after the loop reaction.

[0052] The polymer in the loop is partially recycled through flash gas phase, and the active polymer is transported to the gas phase reactor to continue the reaction. The gas phase reaction conditions are 2.0MPa, 80℃. In the gas phase reactor, the molecular weight of the final product is adjusted by hydrogen, the final density of the product is adjusted by butene, and the molecular weight distribution of the final product is controlled by the distribution rate. The hydrogen / ethylene molar ratio is 4MOL / KMOL, and the butene / ethylene molar ratio is 600MOL / KMOL. The high molecular weight part is produced in the gas phase reactor. The gas phase reaction yield ratio is 57-61, and the powder index of the gas phase reactor is 16-26g / 10min. After the final product produced by the gas phase reactor is inactivated, it enters the extrusion system through the air conveying system for extrusion granulation to form the final polymer particles.

[0053] Example 2: Linear bimodal low density polyethylene

[0054] Ziegler Natta type catalyst is transported to the catalyst preparation tank by nitrogen, and propane is soaked in the catalyst to fill the catalyst micropores with propane. Under the action of propane flushing flow, the catalyst is metered into the prepolymerization reactor, the ethylene addition amount is 350KG / H, the triethylaluminum addition amount is 0.4KG / H, the hydrogen / propane feed ratio is 0.1KG / T, the butene / propane feed ratio is 35KG / T, and the ethylene / catalyst feed ratio is controlled at 300KG / KG. The prepolymerization reaction is carried out at 6.4MPa and 70℃, and a layer of polymer is coated on the catalyst surface to prevent the violent reaction after entering the loop reactor from causing a large number of polymer particles to break and produce a large amount of polymer fine powder.

[0055] The materials in the prepolymerization reactor are connected to the loop reactor at 6.4MPa and 85℃ through the pipeline for reaction. Hydrogen is used to adjust the molecular weight, butene is used to adjust the polymer density of the loop, the hydrogen / ethylene molar ratio is 250MOL / KMOL, the butene / ethylene molar ratio is 600MOL / KMOL, and the amount of triethylaluminum added is 0.6KG / H. Low molecular weight products are produced in the loop reactor, polyethylene after the loop reaction.

[0056] The polymer in the loop is partially recycled through flash gas phase, and the active polymer is transported to the gas phase reactor to continue the reaction. The gas phase reaction conditions are 2.0MPa, 80℃. In the loop reactor, hydrogen is used to adjust the molecular weight of the final product, butene adjusts the final density of the product, and the distribution rate controls the molecular weight distribution of the final product. The hydrogen / ethylene molar ratio is 5MOL / KMOL, and the butene / ethylene molar ratio is 650MOL / KMOL. The high molecular weight part is produced in the gas phase reactor. The gas phase reaction yield ratio is 57-61, and the powder index of the gas phase reactor is 16-26g / 10min. After the final product produced by the gas phase reactor is inactivated, it enters the extrusion system through the air conveying system for extrusion granulation to form the final polymer particles.

[0057] Example 3: Linear bimodal low density polyethylene

[0058] Ziegler Natta type catalyst is transported to the catalyst preparation tank by nitrogen, and propane is soaked in the catalyst to fill the catalyst micropores with propane. Under the action of propane flushing flow, the catalyst is metered into the prepolymerization reactor. The amount of ethylene added is 400KG / H, the amount of triethylaluminum added is 0.5KG / H, the hydrogen / propane feed ratio is 0.1KG / T, the butene / propane feed ratio is 40KG / T, and the ethylene / catalyst feed ratio is controlled at 300KG / KG. The prepolymerization reaction is carried out at 6.4MPa and 70℃. A layer of polymer is coated on the surface of the catalyst to prevent the violent reaction after entering the loop reactor, which causes a large number of polymer particles to break and produce a large amount of polymer fine powder.

[0059] The materials of the prepolymerization reactor are connected through a pipeline to enter a loop reactor at 6.4MPa and 85℃ for reaction. Hydrogen is used to adjust the molecular weight, butene is used to adjust the polymer density of the loop, the hydrogen / ethylene molar ratio is 250MOL / KMOL, the butene / ethylene molar ratio is 600MOL / KMOL, and the amount of triethylaluminum added is 0.7KG / H. Low molecular weight products are produced in the loop reactor, polyethylene after the loop reaction.

[0060] The polymer in the loop is partially recycled through flash gas phase, and the active polymer is transported to the gas phase reactor to continue the reaction. The gas phase reaction conditions are 2.0MPa, 80℃. In the loop reactor, hydrogen is used to adjust the molecular weight of the final product, butene adjusts the final density of the product, and the distribution rate controls the molecular weight distribution of the final product. The hydrogen / ethylene molar ratio is 6MOL / KMOL, and the butene / ethylene molar ratio is 600MOL / KMOL. The high molecular weight part is produced in the gas phase reactor. The gas phase reaction yield ratio is 57-61, and the powder index of the gas phase reactor is 16-26g / 10min. After the final product produced by the gas phase reactor is deactivated, it enters the extrusion system through the air conveying system for extrusion granulation to form the final polymer particles.

[0061] Example 4: Linear bimodal low density polyethylene

[0062] Ziegler-Natta type catalyst is transported to the catalyst preparation tank by nitrogen, and propane is soaked to fill the catalyst micropores with propane. Under the action of propane flushing flow, the catalyst is metered into the prepolymerization reactor, ethylene addition amount is 500KG / H, triethylaluminum addition amount is 0.6KG / H, hydrogen / propane feed ratio is 0.2KG / T, butene / propane feed ratio is 45KG / T, ethylene / catalyst feed ratio is controlled at 400KG / KG, prepolymerization reaction is carried out at 6.4MPa, 70℃, and a layer of polymer is coated on the catalyst surface to prevent the violent reaction after entering the loop reactor from causing a large number of polymer particles to break and produce a large amount of polymer fine powder.

[0063] The materials of the prepolymerization reactor are connected to the loop reactor at 6.4MPa and 85℃ through the pipeline for reaction. Hydrogen is used to adjust the molecular weight, butene is used to adjust the polymer density of the loop, the hydrogen / ethylene molar ratio is 350MOL / KMOL, the butene / ethylene molar ratio is 700MOL / KMOL, and the amount of triethylaluminum added is 0.8KG / H. Low molecular weight products are produced in the loop reactor, polyethylene after the loop reaction.

[0064] The polymer in the loop is partially recycled through flash gas phase, and the active polymer is transported to the gas phase reactor to continue the reaction. The gas phase reaction conditions are 2.0MPa, 80℃. In the loop reactor, hydrogen is used to adjust the molecular weight of the final product, butene adjusts the final density of the product, and the distribution rate controls the molecular weight distribution of the final product. The hydrogen / ethylene molar ratio is 7MOL / KMOL, and the butene / ethylene molar ratio is 700MOL / KMOL. The high molecular weight part is produced in the gas phase reactor. The gas phase reaction yield ratio is 57-61, and the powder index of the gas phase reactor is 16-26g / 10min. After the final product produced by the gas phase reactor is inactivated, it enters the extrusion system through the air conveying system for extrusion granulation to form the final polymer particles.

[0065] Example 5: Linear bimodal low density polyethylene

[0066] Ziegler-Natta type catalyst is transported to the catalyst preparation tank by nitrogen, and propane is soaked to fill the catalyst micropores with propane. Under the action of propane flushing flow, the catalyst is metered into the prepolymerization reactor, ethylene addition amount is 550KG / H, triethylaluminum addition amount is 0.9KG / H, hydrogen / propane feed ratio is 0.2KG / T, butene / propane feed ratio is 50KG / T, ethylene / catalyst feed ratio is controlled at 400KG / KG, prepolymerization reaction is carried out at 6.4MPa, 70℃, and a layer of polymer is coated on the catalyst surface to prevent the violent reaction after entering the loop reactor from causing a large number of polymer particles to break and produce a large amount of polymer fine powder.

[0067] The materials in the prepolymerization reactor are connected through a pipeline to enter a loop reactor at 6.4MPa and 85℃ for reaction. Hydrogen is used to adjust the molecular weight, butene is used to adjust the polymer density of the loop, the hydrogen / ethylene molar ratio is 350MOL / KMOL, the butene / ethylene molar ratio is 700MOL / KMOL, and the amount of triethylaluminum added is 0.9KG / H. Low molecular weight products are produced in the loop reactor, polyethylene after the loop reaction.

[0068] The polymer in the loop is partially recycled through flash gas phase, and the active polymer is transported to the gas phase reactor to continue the reaction. The gas phase reaction conditions are 2.0MPa, 80°C. In the loop reactor, hydrogen is used to adjust the molecular weight of the final product, butene is used to adjust the final density of the product, and the distribution rate controls the molecular weight distribution of the final product. The hydrogen / ethylene molar ratio is 9MOL / KMOL, and the butene / ethylene molar ratio is 700MOL / KMOL. The high molecular weight part is produced in the gas phase reactor. The gas phase reactor yield ratio is 57-61, and the gas phase reactor powder index is 16-26g / 10min. After the final product produced by the gas phase reactor is inactivated, it enters the extrusion system through the air conveying system for extrusion granulation to form the final polymer particles.

[0069] Example 6: Linear Bimodal Low Density Polyethylene

[0070] Ziegler-Natta type catalyst is transported to the catalyst preparation tank by nitrogen, and propane is soaked to fill the catalyst micropores with propane. Under the action of propane flushing flow, the catalyst is metered into the prepolymerization reactor. The amount of ethylene added is 600KG / H, the amount of triethylaluminum added is 1.0KG / H, the hydrogen / propane feed ratio is 0.2KG / T, the butene / propane feed ratio is 50KG / T, and the ethylene / catalyst feed ratio is controlled at 400KG / KG. The prepolymerization reaction is carried out at 6.4MPa and 70℃. A layer of polymer is coated on the surface of the catalyst to prevent the violent reaction after entering the loop reactor, which causes a large number of polymer particles to break and produce a large amount of polymer fine powder.

[0071] The materials of the prepolymerization reactor are connected through a pipeline to enter a loop reactor at 6.4MPa and 85°C for reaction. Hydrogen is used to adjust the molecular weight, butene is used to adjust the polymer density of the loop, the hydrogen / ethylene molar ratio is 350MOL / KMOL, the butene / ethylene molar ratio is 700MOL / KMOL, and the amount of triethylaluminum added is 1.0KG / H. Low molecular weight products are produced in the loop reactor to obtain polyethylene after loop reaction.

[0072] The polymer in the loop is partially recycled through flash gas phase, and the active polymer is transported to the gas phase reactor to continue the reaction. The gas phase reaction conditions are 2.0MPa, 80℃. In the loop reactor, hydrogen is used to adjust the molecular weight of the final product, butene adjusts the final density of the product, and the distribution rate controls the molecular weight distribution of the final product. The hydrogen / ethylene molar ratio is 10MOL / KMOL, and the butene / ethylene molar ratio is 700MOL / KMOL. The high molecular weight part is produced in the gas phase reactor. The gas phase reactor yield ratio is 57-61, and the gas phase reactor powder index is 16-26g / 10min. After the final product produced by the gas phase reactor is inactivated, it enters the extrusion system through the air conveying system for extrusion granulation to form the final polymer particles.

[0073] Test Example 1: Melt Index and Molecular Weight Distribution

[0074] Test sample: linear bimodal low density polyethylene prepared in Examples 1-6;

[0075] Melt flow indexer: Specification: Aflow, Manufacturer: Zwick

[0076] The test was carried out according to the provisions of Method B in GB / T 3682.1-2018. The melt mass flow rate test conditions are as follows:

[0077] Condition T: temperature: 190°C, load: 5.0kg;

[0078] Condition G - Temperature: 190°C, Load: 21.6kg

[0079] Table 2

[0080]

[0081] As shown in the above table, the melt index MFR 5 index of the linear bimodal low density polyethylene prepared in Examples 1-6 is controlled between 0.86 and 1.0, and the melt index MFR 21.6 is controlled between 20.6 and 23.0.

[0082] The molecular weight distribution is characterized by the flow rate ratio FFR, which is based on the ratio of the melt index of the bimodal polyethylene MFR21.6 to MFR5 prepared in Examples 1-6 (flow rate ratio FFR).

[0083] That is, flow rate ratio FFR = MFR21.6 / MFR5

[0084] As shown in the above table, the FFR flow rate ratio of the bimodal polyethylene prepared in Examples 1-6 fluctuates between 22.72 and 23.41, indicating that the molecular weight distribution of the bimodal polyethylene prepared in Examples 1-6 meets the process requirements.

[0085] The size of the FFR flow rate ratio directly characterizes the distribution of molecular weight. The larger the flow rate ratio, the wider the molecular weight distribution, and the smaller the flow rate ratio, the narrower the molecular weight distribution. The low molecular weight part improves the processing performance of the product, and the high molecular weight part gives the product good mechanical properties.

[0086] Test Example 2: Density

[0087] Test samples: polyethylene after loop tube reaction prepared in Example 1-6 and linear bimodal low density polyethylene after gas phase reaction prepared in Example 1-6.

[0088] Densitometer specifications: LLOYD / DC / 02, manufacturer: AMETEK.

[0089] The extruded strips used in the melt flow rate test are used as the samples for density determination. The surface of the samples is smooth, free of gaps and burrs. The strips are immersed in a beaker filled with distilled water, covered with a lid, and boiled in boiling distilled water for 30 minutes for annealing. The beaker is then placed in a laboratory environment and cooled to room temperature. The density of the sample is determined within 24 hours according to the provisions of GB / T 1033.2-2010.

[0090] Table 3

[0091]

[0092] As can be seen from the above table, the density of the linear bimodal low-density polyethylene prepared in Examples 1-6 after the loop reaction is controlled at 0.949-0.951, and the density fluctuates within a reasonable range, indicating that the density control achieved by the butene / ethylene ratio in Examples 1-6 is stable and effective;

[0093] The density of the linear bimodal low-density polyethylene prepared in Example 1-6 after the gas phase reaction was controlled at 0.9229-0.9231, and the density was stable without abnormal fluctuation.

[0094] Application Example 1:

[0095] The industrial application of bimodal linear film materials in heavy-duty packaging bags adopts the SC7530S blow molding machine of Hanwang Plastic Machinery Co., Ltd. in Taiwan, China. The blow molding machine blows to form heavy-duty packaging films. The linear bimodal low-density polyethylene prepared in Example 1 with a weight ratio of 22:15:50:13: MM2002: metallocene linear low-density polyethylene: HDPE is configured to obtain 0.12mm and 0.14mm heavy-duty packaging bag films for use.

[0096] Application Example 2:

[0097] The industrial application of bimodal linear film materials in heavy-duty packaging bags uses an SC7530S blow molding machine from Hanwang Plastic Machinery Co., Ltd. in Taiwan, China. The blow molding machine blows heavy-duty packaging films. FB2230:FB1350:metallocene linear low-density polyethylene:HDPE with a weight ratio of 22:15:50:13 is configured to obtain a 0.14mm heavy-duty packaging bag film for use.

[0098] Test Example 3: Tensile Strength

[0099] Test sample: Heavy packaging film prepared in Application Example 1 and Application Example 2

[0100] Name: Universal material testing machine, Specification: Roell Z005, Manufacturer: ZWICK

[0101] The state adjustment of the sample is carried out in accordance with GB / T 2918-2018. The state adjustment conditions are 23℃±2℃, 50%±10% relative humidity, and 40h adjustment time. The test is carried out under the standard environment specified in GB / T 2918-2018, with an environmental temperature of 23℃±2℃ and a relative humidity of 50%±10%. The test is carried out in accordance with GB / T 1040.3-2006. The sample meets the requirements of Type 2 in GB / T 1040.3-2006. The test speed is (500±50)mm / min and the gauge length is (50±0.5)mm.

[0102] Table 4

[0103]

[0104] It can be seen from the above table that the 0.12mm heavy packaging film and 0.14mm heavy packaging film prepared in Application Example 1 are close to the 0.14mm heavy packaging film prepared in Application Example 2 in terms of longitudinal tensile strength and transverse tensile strength, indicating that by using the same proportion of linear bimodal low-density polyethylene to replace the Nordic chemical product FB2230, the Nordic film material can be replaced in proportion.

[0105] Moreover, the heavy packaging film prepared in Application Example 1 also has good processing performance, thereby achieving effective thinning during the processing and production of heavy packaging bags. The thickness of the heavy packaging film bag can be thinned from 0.18MM to 0.12-0.14MM, which can effectively reduce the use of polyethylene raw materials and achieve energy saving and consumption reduction.

[0106] Test Example 4: Nominal strain at break

[0107] Test sample: Heavy packaging film prepared in Application Example 1 and Application Example 2

[0108] Equipment for fracture nominal strain test: universal material testing machine, specification: Z0.5TH, manufacturer: ZWICK. The state adjustment of the specimen is carried out in accordance with GB / T 2918-2018. The state adjustment conditions are temperature 23℃±2℃, relative humidity 50%±10%, and adjustment time 40h.

[0109] The test was carried out under the standard environment specified in GB / T 2918-2018, with an ambient temperature of 23°C ± 2°C and a relative humidity of 50% ± 10%.

[0110] The specimen complies with the requirements of GB / T 16578.1-2008, and the thickness of the specimen is 15μm±3μm.

[0111] The test is carried out in accordance with GB / T 16578.1-2008, and the test speed is (200±20) mm / min.

[0112] Table 5

[0113]

[0114] It can be seen from the above table that the 0.12mm heavy packaging film and 0.14mm heavy packaging film prepared in Application Example 1 and the 0.14mm heavy packaging film prepared in Application Example 2 are relatively close in the longitudinal nominal strain at break and the transverse nominal strain at break, indicating that by using the same proportion of linear bimodal low-density polyethylene to replace the Nordic chemical product FB2230, the Nordic film material can be replaced in proportion.

[0115] Moreover, the heavy packaging film prepared in Application Example 1 also has good processing performance, thereby achieving effective thinning during the processing and production of heavy packaging bags. The thickness of the heavy packaging film bag can be thinned from 0.18MM to 0.12-0.14MM, which can effectively reduce the use of polyethylene raw materials and achieve energy saving and consumption reduction.

[0116] Test Example 5: Right Angle Tear Strength

[0117] Test sample: Heavy packaging film prepared in Application Example 1 and Application Example 2

[0118] Tearing tester: SLD-S1 Mile Instrument, the specimen complies with the requirements of GB / T16578.2-2009.

[0119] Table 6

[0120]

[0121] As can be seen from the above table, the 0.12mm heavy packaging film and 0.14mm heavy packaging film prepared in Application Example 1 and the 0.14mm heavy packaging film prepared in Application Example 2 are relatively close in longitudinal right-angle tear strength and transverse right-angle tear strength, indicating that by using the same proportion of linear bimodal low-density polyethylene to replace the Nordic chemical product FB2230, the Nordic film material can be replaced in proportion.

[0122] Moreover, the heavy packaging film prepared in Application Example 1 also has good processing performance, thereby achieving effective thinning during the processing and production of heavy packaging bags. The thickness of the heavy packaging film bag can be thinned from 0.18MM to 0.12-0.14MM, which can effectively reduce the use of polyethylene raw materials and achieve energy saving and consumption reduction.

[0123] In summary, it can be seen from Tables 4-6 that there is no significant difference in the mechanical properties between the heavy packaging film prepared in Application Example 1 of the present invention and the heavy packaging film prepared in Application Example 2. The mechanical properties tests of the 0.12 mm heavy packaging film are close to those of the 0.14 mm heavy packaging film, which fully meets the requirements of market applications.

[0124] After adding the bimodal linear low-density polyethylene prepared by the present invention, the heavy packaging film has good mechanical properties such as tear strength and tensile strength. Under the condition of bearing the same weight or external force, the thickness of the heavy packaging film can be reduced, the amount of raw materials used can be reduced, and the effect of energy saving and consumption reduction can be achieved.

[0125] Since the bimodal linear low density polyethylene prepared by the present invention has good mechanical properties such as impact strength and tensile strength, the thickness of the heavy packaging film can be reduced from the original 0.18MM (the linear bimodal low density polyethylene described in the present invention is not added during the processing of the heavy packaging film) to 0.14MM or even 0.12MM without affecting the quality and life of the heavy packaging bag.

[0126] Test Example 6:

[0127] Test sample: Heavy packaging film prepared in Application Example 1

[0128] The heavy packaging film prepared in Application Example 1 of the present invention can not only meet the continuous operation requirements of high-speed packaging machines, but also meet the continuous operation requirements of high-speed packaging machines due to the addition of the bimodal linear low-density polyethylene prepared in the present invention.

[0129] The product was applied to polyethylene and polypropylene common 25kg packaging products, and the bag drop test and stacking performance experiment were carried out.

[0130] 0.12mm and 0.14mm heavy packaging films were prepared using Application Example 1. No abnormal situation occurred during the production process, the film opening was good, the production was stable, and the thickness could be stably controlled. The produced 0.12mm heavy packaging film was tested in the 2PP-A packaging workshop of Shanghai Petrochemical. The heat sealing temperature was lowered by 10℃ compared with the 0.14mm thick heavy film. The heat sealing temperature was 130-135℃, the sealing was neat, the friction coefficient met the requirements of climbing and stacking, and the stacking was neat.

[0131] The 0.14mm heavy packaging film was tried out on the 3PP-D packaging line. The sealing temperature was the same as that of the original heavy film, the sealing was neat, the friction coefficient met the requirements for climbing and palletizing, and the palletizing was neat.

[0132] The 25KG packaged polypropylene was subjected to a drop test. The 0.12mm thick heavy film was broken 5 times after free fall from a height of 3 meters, and the 0.14mm thick film was broken 7 times after free fall from a height of 3 meters. The drop resistance performance meets the user's requirements.

[0133] After inspection of logistics transportation and user application, the long-distance transportation process can still maintain a good stacking shape, without deformation or broken packages, and no increase in damage occurs. In the packaging of synthetic resin products, the 0.14mm thick heavy packaging film is optimized and thinned to 0.12mm, which reduces the amount of raw materials by about 10% and achieves the effect of energy saving and consumption reduction.

[0134] Application Example 3:

[0135] The bimodal linear low-density polyethylene film material prepared in the embodiment of the present invention can be used not only for the production and processing of heavy packaging films but also for the production and processing of electrical (optical) cable sheath materials. It can effectively improve the mechanical properties (tensile strength, dart impact strength, tear strength, etc.) of the product while having good processing performance.

Claims

1. A bimodal linear low density polyethylene, characterized in that The density of the bimodal linear low-density polyethylene is 0.915-0.930 g / cm 3 , preferably with a density of 0.918-0.924 g / cm 3 .

2. The bimodal linear low density polyethylene according to claim 1, characterized in that The bimodal linear low-density polyethylene has a melt index MFR 21.6 between 18 and 25 G / MIN, a melt index MFR 5 between 0.80 and 1.2 G / MIN, and a flow rate ratio FFR of 20 to 30.

3. A method for preparing a bimodal linear low-density polyethylene as claimed in any one of claims 1 to 2, characterized in that: The method comprises the following steps: 1) prepolymerizing ethylene, butene, hydrogen, catalyst and triethylaluminum in a weight ratio of 300-600:30-50:0.1-0.2:300-400:0.3-1.0 at 6.4 MPa and 70° C. to obtain a prepolymer; 2) subjecting the prepolymer of step 1) to a ring tube reaction at 6.4 MPa and 85° C., and adding hydrogen, ethylene, butene and triethylaluminum in a molar ratio of 250-350:1000:600-700:0.5-1.0 to obtain a ring tube reaction polymer; 3) The polymer obtained in the loop reaction in step 2) is subjected to gas phase reaction at 2.0 MPa and 80° C., and hydrogen, ethylene and butene are added in a molar ratio of 4-10:1000:600-700 to obtain a bimodal linear low density polyethylene.

4. The method according to claim 3, characterized in that The catalyst in step 1) is a Ziegler-Natta type catalyst.

5. The method according to claim 4, characterized in that In step 1), the catalyst is transported by nitrogen and is soaked in propane so that the catalyst micropores are filled with propane. Under the action of the propane flushing flow, the catalyst enters the prepolymerization reaction.

6. The method according to claim 3, characterized in that The melt index MFR 21.6 of the loop reaction polymer in step 2) is between 250-350 G / MIN, and the density is 0.948-0.953 g / cm3.

7. The method according to claim 3, characterized in that The gas phase reaction yield ratio in step 3) is 57-61.

8. The method according to claim 7, characterized in that The gas phase reaction powder index in step 3) is 16-26 g / 10 min.

9. Use of the bimodal linear low-density polyethylene as claimed in any one of claims 1 to 2 in the fields of heavy packaging films, electrical and / or optical cable sheathing materials, etc.

10. A heavy packaging film, characterized in that: The heavy packaging film comprises the bimodal linear low density polyethylene, linear medium density polyethylene, metallocene linear low density polyethylene and HDPE according to any one of claims 1 to 2 in a weight ratio of 22:15:50:

13.

11. The heavy packaging film according to claim 10, characterized in that: The thickness of the heavy packaging film is ≤0.14 mm.

12. The heavy packaging film according to claim 11, characterized in that: The thickness of the heavy packaging film is 0.12mm-0.14mm.

13. The heavy packaging film according to claim 10, characterized in that: The longitudinal tensile strength of the heavy packaging film is 35-36 MPa, and the transverse tensile strength is 28-29 MPa.

14. The heavy packaging film according to claim 10, characterized in that: The nominal strain at break of the heavy packaging film in the longitudinal direction is 755-816%, and the nominal strain at break in the transverse direction is 985-1095%.

15. The heavy packaging film according to claim 10, characterized in that: The heavy packaging film has a longitudinal right-angle tear strength of 167-175 KN / m, and a transverse right-angle tear strength of 256-281 KN / m.

Citation Information

Patent Citations

  • Impact resistant LLDPE composition and films made thereof

    US8846188B2

  • Impact resistant LLDPE composition and films made thereof

    US8957158B2

  • Serological biomarkers for early diagnosis of lung cancer

    WO2020069637A1

  • Bimodal linear low density polyethylene copolymer

    WO2021202483A1

  • Bimodal linear low density polyethylene copolymer

    WO2021202486A1